2021
DOI: 10.3390/ijms22116094
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Analyses Validate Human MicroRNAs Targeting the SARS-CoV-2 3′-UTR

Abstract: COVID-19 pandemic is caused by betacoronavirus SARS-CoV-2. The genome of this virus is composed of a single strand of RNA with 5′ and 3′-UTR flanking a region of protein-coding ORFs closely resembling cells’ mRNAs. MicroRNAs are endogenous post-transcriptional regulators that target mRNA to modulate protein expression and mediate cellular functions, including antiviral defense. In the present study, we carried out a bioinformatics screening to search for endogenous human microRNAs targeting the 3′-UTR of SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…According to previously published papers, the binding of miRNAs to the viral genome may reduce the levels of free miRNAs in the cell, and it has been recently reported that COVID patients may develop an Alzheimer’s-like disease [ 51 ]. Moreover, the ability of hsa-miR-3941 to target the SARS-CoV-2 3′-UTR was recently validated in vitro by gene reporter assays [ 52 ]. The antiviral effects of miR-122 and miR-148-3p against HCV virus infections have been shown [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previously published papers, the binding of miRNAs to the viral genome may reduce the levels of free miRNAs in the cell, and it has been recently reported that COVID patients may develop an Alzheimer’s-like disease [ 51 ]. Moreover, the ability of hsa-miR-3941 to target the SARS-CoV-2 3′-UTR was recently validated in vitro by gene reporter assays [ 52 ]. The antiviral effects of miR-122 and miR-148-3p against HCV virus infections have been shown [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“… ( Mi et al, 2021 ) miR-200c-3p Bioinformatics ACE2 miR-200 family members are strong candidate targets for the regulation of ACE2 respiratory system cell. ( Bozgeyik, 2021 ) miR-3941 and hsa-miR-138-5p In silico, in vitro, bioinformatics SARS-CoV-2 3′UTR These microRNAs show antiviral or protective effects in the host cells, making them potential candidates for therapeutic treatment ( Barreda-Manso et al, 2021 ) hsa-miR-342-5p, hsa-miR-432-5p, hsa-miR-98-5p and hsa-miR-17-5p Bioinformatics Host genes (MYC, IL6, ICAM1 and VEGFA) and SARS-CoV2 gene (ORF1ab) These miRNAs target multiple host and SARS-CoV2 genes and can be novel personalized therapeutic targets for COVID-19 patients. ( Banaganapalli et al, 2021 ) miR-10b In vivo COVID-19 patients and healthy subjects 62 Blood samples IL-2 and IL-8 miR-10b is downregulated in the blood samples of COVID-19 patients and can contribute to cytokine storms by increasing IL-2 and IL-8 ( Bagheri-Hosseinabadi et al, 2021 ) miR-124-3p Bioinformatics A ceRNA network involving one miRNA (miR-124-3p), one mRNA (Ddx58), one lncRNA (Gm26917) and two circRNAs (Ppp1r10, C330019G07RiK) in SARS-CoV infected cells is predicted.…”
Section: Dysregulated Mirnas In Covid-19mentioning
confidence: 99%
“…These deregulated host miRNA by targeting 3 -untranslated regions of host PCG and could modify innate immunity, inflammation, viral replication, etc., and were reviewed recently [52][53][54]. Various host microRNA has been identified by computational methods to bind with the SARS-CoV-2 RNA Genome [55][56][57][58]. SARS-CoV-2 might code microRNA that could regulate the host gene [59][60][61] These in silico analyses and limited experimental results revealed the role of microRNA as a potential marker for SARS-CoV-2 infection, as well as a target for the treatment of COVID-19 [62].…”
Section: Deregulation Of Microrna and Circular Rnas In Sars-cov-2 Inf...mentioning
confidence: 99%